Changes in blood gas transport of altitude native soccer players near sea-level and sea-level native soccer players at altitude (ISA3600) - Wachsmuth, N.; Kley, M.; Spielvogel, H.; Aughey, R. J.; Gore, C. J.; Bourdon, P. C.; Hammond, K.; Sargent, C.; Roach, G. D.; Sanchez, R. S.; Claros, J. C. J.; Schmidt, W. F.; et al. (British Journal of Sports Medicine, 2013)
Objectives: The optimal strategy for soccer teams playing at altitude is not known, that is, `fly-in, fly-out` versus short-term acclimatisation. Here, we document changes in blood gas and vascular volumes of sea-level (Australian, n=20) and altitude (Bolivian, n=19) native soccer players at 3600 m. Methods: Haemoglobin-oxygen saturation (Hb-sO2), arterial oxygen content (CaO2), haemoglobin mass (Hbmass), blood volume (BV) and blood gas concentrations were measured before descent (Bolivians only), together with aerobic fitness (via Yo-YoIR1), near sea-level, after ascent and during 13 days at 3600 m.Results At baseline, haemoglobin concentration [Hb] and Hbmass were higher in Bolivians (mean±SD; 18.2±1.0 g/dL, 12.8±0.8 g/kg) than Australians (15.0±0.9 g/dL, 11.6±0.7 g/kg; both p=0.001). Near sea-level, [Hb] of Bolivians decreased to 16.6±0.9 g/dL, but normalised upon return to 3600 m; Hbmass was constant regardless of altitude. In Australians, [Hb] increased after 12 days at 3600 m to 17.3±1.0 g/dL; Hbmass increased by 3.0±2.7% (p=0.01). BV decreased in both teams at altitude by ~400 mL. Arterial partial pressure for oxygen (PaO2), Hb-sO2 and CaO2 of both teams decreased within 2 h of arrival at 3600 m (p=0.001) but increased over the following days, with CaO2 overcompensated in Australians (+1.7±1.2 mL/100 mL; p=0.001). Yo-YoIR1 was lower on the 3rd versus 10th day at altitude and was significantly related to CaO2. Conclusions The marked drop in PaO2 and CaO2 observed after ascent does not support the `fly-in, fly-out` approach for soccer teams to play immediately after arrival at altitude. Although short-term acclimatisation was sufficient for Australians to stabilise their CaO2 (mostly due to loss of plasma volume), 12 days appears insufficient to reach chronic levels of adaption.